2023
DOI: 10.3390/ijms24129819
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester and Caffeamide Derivatives Suppress Oral Squamous Cell Carcinoma Cells

Abstract: Caffeic acid phenethyl ester (CAPE) contains antibiotic and anticancer activities. Therefore, we aimed to investigate the anticancer properties and mechanisms of CAPE and caffeamide derivatives in the oral squamous cell carcinoma cell (OSCC) lines SAS and OECM-1. The anti-OSCC effects of CAPE and the caffeamide derivatives (26G, 36C, 36H, 36K, and 36M) were evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test. Cell cycle and total reactive oxygen species (ROS) production were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Blocking autophagy did not reduce ROS generation, which is consistent with our results and places ROS upstream of autophagy. Recently, several reports indicated that anticancer agents induced ROS production followed by activation of autophagy and induction of autophagic cell death in oral squamous cell carcinoma, prostate cancer, and CRC cells [ 26 , 27 , 28 ]. However, the exact mechanism by which autophagy achieves this outcome remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking autophagy did not reduce ROS generation, which is consistent with our results and places ROS upstream of autophagy. Recently, several reports indicated that anticancer agents induced ROS production followed by activation of autophagy and induction of autophagic cell death in oral squamous cell carcinoma, prostate cancer, and CRC cells [ 26 , 27 , 28 ]. However, the exact mechanism by which autophagy achieves this outcome remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was described in previous research. 13 Briefly, cell lysates were denatured using 5x SDS sample loading buffer at 95 °C for 5 min and loaded onto 10% SDS-PAGE gels with approximately 10 μg of total protein per lane. The separated proteins were transferred onto Polyvinylidene difluoride (PVDF) membranes, and subsequent blocking was performed with 5% non-fat dry milk in Tris-buffered saline containing 0.1% Tween 20 for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA levels were analyzed using the Applied Biosystems StepOnePlus™ Real-Time PCR System (Thermo Fisher Scientific, Waltham, MA, USA). All reactions were performed in triplicate, and relative gene expressions were quantified by normalizing to that of GAPDH and calculated using the 2 −∆∆Ct method [29].…”
Section: Reverse Transcription and Quantitative Real-time Pcr Analysi...mentioning
confidence: 99%